Emergency in Malaya and Reaction of The United States, 1948-1960 - Ismail, Noorilham; Zakariah, Muhamad Hasrul (European Publisher, 2019)
This paper provides an analysis on the United States’ (US) reaction towards the Malayan emergency that occurred between 1948 and 1960. From the US’ perspective, the emergency in Malaya was a problem that resulted from the communist movement. The core objective of this paper is to explore the United States’ reaction and the reasons for this reaction. Apart from that, this paper will also focus on the United States’ actions following the reaction they had taken, which can be observed through documents such as the Foreign Relations of the United States (FRUS), the Department of State Bulletin, the Pentagon Papers, reports from the Central Intelligence Agency (CIA), British documents and memoirs from local and overseas archives. Based on these documents, the reaction towards the Malayan emergency by the United States can be directly and indirectly concluded. The methods used in this paper involved source researching in archives, document analysis, translating files and interpreting resources. The United States’ reaction towards the Malayan emergency is closely related to regional communist threats and conflicts in the Far East. This paper will argue that ideological competition and strategic considerations were seen as reasons or factors that affected the United States’ reaction towards the emergency. Finally, this paper will further argue that the United States’ reaction towards the Malayan emergency from 1948 to 1960 was significant in diminishing communist threats in Southeast Asia and in Malaya.